Flow goes forward and cells step backward: endothelial migration - Lee, Heon-Woo; Shin, Jae Hun; Simons, Michael (Experimental & molecular medicine, 2022)
Systemic and pulmonary circulations constitute a complex organ that serves multiple important biological functions. Consequently, any pathological processing affecting the vasculature can have profound systemic ramifications. Endothelial and smooth muscle are the two principal cell types composing blood vessels. Critically, endothelial proliferation and migration are central to the formation and expansion of the vasculature both during embryonic development and in adult tissues. Endothelial populations are quite heterogeneous and are both vasculature type- and organ-specific. There are profound molecular, functional, and phenotypic differences between arterial, venular and capillary endothelial cells and endothelial cells in different organs. Given this endothelial cell population diversity, it has been challenging to determine the origin of endothelial cells responsible for the angiogenic expansion of the vasculature. Recent technical advances, such as precise cell fate mapping, time-lapse imaging, genome editing, and single-cell RNA sequencing, have shed new light on the role of venous endothelial cells in angiogenesis under both normal and pathological conditions. Emerging data indicate that venous endothelial cells are unique in their ability to serve as the primary source of endothelial cellular mass during both developmental and pathological angiogenesis. Here, we review recent studies that have improved our understanding of angiogenesis and suggest an updated model of this process. Blood vessel formation: Migratory cells lining veins key to growth Cells that line the inside of veins possess a unique ability to grow new blood vessels and a better understanding of these cells could lead to new treatments for cancer, autoimmunity and other diseases associated with abnormal blood vessel formation. Michael Simons and colleagues from Yale University School of Medicine in New Haven, USA, review the attributes of venous endothelial cells, such as their unique ability to proliferate and migrate against blood flow, and then to form new intricate networks of minute blood vessels, in response to appropriate signals. The authors discuss emerging evidence implicating these cells in a variety of diseases, and suggest that drugs aimed at modulating the molecular function or migratory activities of venous endothelial cells could be used to correct abnormal blood vessel expansion.